(Re)categorizing Intergroup Relations and Social Identities Through News Discourse: The Case of the China Daily's Reporting on Regional Conflict. (March 2014) - Chan, Michael
Drawing from social psychology perspectives of intergroup relations, including the common in-group identity model, mutual intergroup differentiation model, and optimal distinctiveness theory, this study proposes a theoretical framework of news analysis that accounts for the socially structured and hierarchical nature of international relations. The coverage of the territorially disputed Diaoyu/Senkaku Islands by the China Daily from 2002 to 2011 serves as the context for the framework. Integrated content, discourse, and concordance analyses showed that despite the local nature of the dispute that invokes clear in-group/out-group categorizations, the majority of the articles in the newspaper discursively recategorize intergroup relations, including the assimilation of Japan under a superordinate "Asian" identity and the categorization of the United States as the "outsider" purposefully interfering in China–Japan relations. The findings provide important ideological insights of the ruling party state and its attempts to influence intergroup comparisons by reconfiguring the basis of intergroup evaluation and differentiation.